2014
DOI: 10.1007/s10867-014-9342-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of screening and treatment in the transmission dynamics of HIV/AIDS and tuberculosis co-infection: a mathematical study

Abstract: In this paper, we present a deterministic non-linear mathematical model for the transmission dynamics of HIV and TB co-infection and analyze it in the presence of screening and treatment. The equilibria of the model are computed and stability of these equilibria is discussed. The basic reproduction numbers corresponding to both HIV and TB are found and we show that the disease-free equilibrium is stable only when the basic reproduction numbers for both the diseases are less than one. When both the reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Agusto et al [91] considered optimal control theory applied to a two-(TB)strain TB/HIV ODE model. Kaur et al [92] studied an ODE TB/HIV model that includes abstractly defined screening and treatment interventions from a dynamical systems perspective. Sharomi et al [93] also applied dynamical systems analysis to a TB/HIV ODE model, but with more explicit representation of intervention strategies including ART.…”
Section: Population-level Impact Of Interventionsmentioning
confidence: 99%
“…Agusto et al [91] considered optimal control theory applied to a two-(TB)strain TB/HIV ODE model. Kaur et al [92] studied an ODE TB/HIV model that includes abstractly defined screening and treatment interventions from a dynamical systems perspective. Sharomi et al [93] also applied dynamical systems analysis to a TB/HIV ODE model, but with more explicit representation of intervention strategies including ART.…”
Section: Population-level Impact Of Interventionsmentioning
confidence: 99%
“…, it is easy to show that the set Ω 2 is positively invariant and a global attractor of all positive solutions of submodel (9). Hence, it is sufficient to consider the dynamics of model (9) in Ω 2 as epidemiologically and mathematically wellposed.…”
Section: Pneumonia Submodel Analysis From Model (4) We Have Got the Pneumonia Submodel Atmentioning
confidence: 99%
“…AIDS is a common individual immune system disease caused by human immunodeficiency virus (HIV), i.e., RNA retrovirus which has developed into a global pandemic since the first patient was identified in 1981, making it one of the most destructive epidemics in history. HIV attacks human white blood cells and is transmitted through open sex, needle sharing, infected blood, and at childbirth [3,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Over two-thirds of people living with HIV live in the Sub-Saharan African region [4]. Human immunodeficiency virus (HIV) is a retrovirus virus which attacks and weakens the human body immunity and the central nervous system and if untreated it continues to multiply into the host until it reaches the peak leading into a very serious disease called AIDS, the stage where the symptoms of the disease occur frequently [5][6][7]. HIV is transmitted through sexual intercourse, needle sharing, and direct contact of blood or other body fluids containing the virus and mother to child during childbirth [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…They have got the treatment of primary and secondary syphilis in both singly and dually infected individuals; especially with high treatment rates for primary syphilis, this will result in a reduction in the incidence of HIV and its coinfection with syphilis in the community. Kaur et al [6] formulated and analyzed a mathematical model for HIV/AIDS-TB coinfection with screening and treatment of both HIV and TB infective. Their numerical results suggested that the rates of transmission of both TB and HIV should be decreased, as an increase causes a rise in the number of infective at the equilibrium level.…”
Section: Introductionmentioning
confidence: 99%